Case studies on community care in Japan: considerations for mitigating social isolation and loneliness in older adults with dementia - Li-Mei Chen; Megumi Inoue; Nina Buckley (Frontiers Media S.A., 2024)
This article explores dementia care in Japan's aging population with a focus on mitigating social isolation and loneliness in older adults with dementia. Through an in-depth examination of case studies, the study highlights several community-based interventions, including Community Cafés, the Dementia Supporter Caravan, and the Omuta City Dementia Care model. These cases provide insights into how these initiatives foster community engagement and inclusive environments. Using a socio-ecological (SE) framework, the analysis focuses on the effectiveness of leveraging social capital to address the social challenges faced by people living with dementia (PLwD) and their caregivers. The case studies emphasize context-sensitive strategies tailored to Japan's cultural and demographic landscape, offering lessons for reducing isolation and promoting community support for older adults with dementia.